TANGGUNG JAWAB PEMENUHAN HAK – HAK PEKERJA OLEH PERUSAHAAN YANG TELAH PAILIT (STUDI KASUS PT. AIRLANGGA SAWIT JAYA DI KABUPATEN LANDAK) - NIM. A1011191169, REGINA IRENE TINAMBUNAN (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract Bankruptcy is a condition in which the debtor is unable to make payments on the debts of his creditors. The condition of not being able to pay is usually caused by difficulties in the financial condition of the debtor's business which has experienced setbacks. In this condition, apart from having difficulty repaying debts to creditors, companies also experience difficulties in fulfilling workers' or laborers' rights. Like what happened to PT. Airlangga Sawit Jaya, which went bankrupt on December 19 2019. The bankruptcy of PT. Airlangga Sawit Jaya so that the company does not fulfill the rights of workers, namely not paying severance pay for workers who terminate work relations. Thus a team of curators was formed to take care of bankruptcy assets and settle debts to creditors, especially employees who are preferred creditors. The formulation of the problem in this study is: